The Bond van Oudgeïnterneerdes en Politieke Gevangenes as a Direct and Long-Lasting Social Manifestation Related to the Internment Policy of the Union of South Africa, 1946–1985 - La Grange, Anna (Scientia Militaria - South African Journal of Military Studies, 2023)
During the Second World War, the Union of South Africa implemented emergency regulations, including an internment policy, to curb anti-war efforts within South Africa. These regulations and internment policy affected one of the biggest anti-war organisations, the Ossewabrandwag (OB), and many of its members were detained during the war in internment camps. In 1946, the Bond van Oud-geïnterneerdes en Politieke Gevangenes (BOPG) was formed by individuals, mostly OB members, who were interned in South African internment camps. Using the BOPG collection that forms part of the Ossewabrandwag-archives, this article explores some similarities between the Memorable Order of Tin Hats (MOTH) and the BOPG in post-Second World War South Africa, it provides a brief historical background to the BOPG, and explores some key themes and focuses within the organisation. By framing the BOPG as a direct and long-lasting social manifestation related to the Union of South Africa’s internment policy, this article constitutes a first attempt at exploring the BOPG and understanding its role in the larger picture of South Africa’s Second World War experiences and memories.